2018
DOI: 10.3389/fncel.2018.00430
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cerebellar Gray Matter Atrophy Across Alzheimer’s Disease Progression

Abstract: The role of the cerebellum in cognitive function has been broadly investigated in the last decades from an anatomical, clinical, and functional point of view and new evidence points toward a significant contribution of the posterior lobes of the cerebellum in cognition in Alzheimer’s disease (AD). In the present work we used SUIT-VBM (spatially unbiased infratentorial template, voxel-based morphometry) to perform an analysis of the pattern of cerebellar gray matter (GM) atrophy in amnestic mild cognitive impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Additionally, differences were observed among groups in the case of the cerebellum, where lower activation was detected in later stages of the disease. In line with our results, recent studies have highlighted the role of cerebellum in the AD hypothesis and its pivotal role in cognitive impairment [129,130]. Our findings support and underline the importance of a reasonable and consistent interchange among particular brain areas and support that interruption or any disconnection in these specific regions may be linked to the future development of AD.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, differences were observed among groups in the case of the cerebellum, where lower activation was detected in later stages of the disease. In line with our results, recent studies have highlighted the role of cerebellum in the AD hypothesis and its pivotal role in cognitive impairment [129,130]. Our findings support and underline the importance of a reasonable and consistent interchange among particular brain areas and support that interruption or any disconnection in these specific regions may be linked to the future development of AD.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous literature our results do not show a significant difference in cerebellar volume between healthy individuals and aMCI patients [71,72]. Recent work suggested that the Crus I would show atrophy late in the disease process [73] leaving us to speculate that functional connectivity changes of the cerebellar-cerebral DMN precede atrophy of the cerebellar DMN region. Since the association with memory was only observed for the frontal region and not the medial temporal regions and no association was shown with executive functioning, we propose-in keeping with the dysmetria of thought hypothesis [74,75]-that the cerebellum has a modulating role on the executive components of memory performance.…”
Section: Discussionsupporting
confidence: 92%
“…It is indeed very significant that a recent study of another animal model of AD (the 5xFAD) shows amyloid plaques accumulation in the spinal cord tissue, with a particular concentration at cervical level and a time-dependent accumulation that starts 11 weeks from onset; interestingly, the same study found independent and extensive myelopathy, while the motoneurons count at 6 months was not altered compared to the wild type (Chu et al, 2017). While, we cannot be conclusive on the mechanisms of spinal cord atrophy in AD, our results are intriguing and calling for larger studies of prodromic subjects to be followed over time; such studies would also confirm whether the suggestion that the motor system (neocortex, cerebellum and spinal cord) is affected even before the cognitive one can be substantiated, or whether the spinal cord is following similar pathophysiological global changes as brain structures (Agosta et al, 2010;Albers et al, 2015;Toniolo et al, 2018). A further result of our work is that of all spinal cord features analyzed here, the area of vertebra C2-C3 (CSA23) significantly contributes to discrimination between HC and AD patients.…”
Section: Explained Variancementioning
confidence: 65%
“…Optical Coherence Tomography studies, for example, have been used to demonstrate that retinal ganglion cell degeneration can be associated with early stages of AD. Also, structures like the cerebellum, not classically associated with AD, have been found to be altered in imaging studies of dementia (Castellazzi et al, 2014), with atrophy of the anterior cerebellum-known for its motor control-being present even in the prodromic stages of mild cognitive impairment (MCI; Toniolo et al, 2018). Recent work has also looked at graph theory metrics to distinguish patterns of AD, identifying potentially different subtypes (Ferreira et al, 2019), although focusing on cortical and deep gray matter areas, without including the cerebellum and the spinal cord.…”
Section: Introductionmentioning
confidence: 99%